THE EFFECT OF MOTIVATION AND JOB TRAINING ON IMPROVING TEACHER COMPETENCE AND PERFORMANCE AT “AAA" PRIVATE SCHOOLS IN MAKASSAR CITY. - Naftalli Suzan; Dian Parawansa; Fauziah Umar (Hasanuddin Journal of Applied Business and Entrepreneurship, 2021)
This study aims to determine the effect of motivation and job training on improving teacher competence and performance at "AAA" private school in Makassar City. The research used a quantitative approach. The populations were all teachers consisting of 90 people. The data were obtained through observation and questionnaires. Data were analyzed using path analysis. The results of the research indicate that (1) work motivation has a positive and significant effect on increasing teacher competence at "AAA" private school in Makassar City; (2) job training has a negative and insignificant effect on increasing teacher competence at "AAA" private school in Makassar City; (3) work motivation has a positive and significant effect on teacher performance at "AAA" private school in Makassar City; (4) job training has a positive and insignificant effect on teacher performance at "AAA" private school in Makassar City; (5) teacher competence has a positive and significant effect on improving teacher performance at "AAA" private school in Makassar City; (6) work motivation indirectly has a positive and significant effect on teacher performance through teacher competence at "AAA" private school in Makassar City; (7) job training indirectly has a negative and insignificant effect on teacher performance through teacher competence at "AAA" private school in Makassar City.